Review: The Cambridge Companion to Feminist Theology - Muers, Rachel (The journal of theological studies, 2004)
The Cambridge Companion to Feminist Theology. Susan Frank Parsons Pp. xviii+268 Cambridge Cambridge University Press 2002 0 521 66327 x and 66380 6. Hardback £ 40/ $55 ; paper £ 14.95/ $20